Quality traits analysis of 153 wheat lines derived from CIMMYT and China - Liu, Pengpeng; Zhang, Zhe; Yin, Yuruo; Yan, Shanshan; Ren, Yong; Sang, Wei; Xu, Hongjun; Han, Xinnian; Cui, Fengjuan; Nie, Yingbin; Kong, Dezhen; Li, Wei; et al. (Frontiers in Genetics, 2023)
In order to understand the difference of quality for Chinese and CIMMYT wheat varieties (lines), we selected 153 wheat germplasm from both China and CIMMYT to explore the contribution relationship of different allelic variation combinations to wheat quality through genotyping and phenotyping, including grain hardness, polyphenol oxidase (PPO) activity, lipoxygenase (LOX) activity, yellow pigment (YP) content and protein content. In terms of flour milling quality, Chinese wheat varieties were mainly carrying Pina-D1a/Pinb-D1b, accounting for 32.0% of the total tested varieties, while the CIMMYT wheat lines were mainly carrying Pina-D1b/Pinb-D1a with 45.8% of the total collection. The distribution frequencies of subunit 1/2* and 5+10 were 47.0% and 42.5%, respectively, in CIMMYT varieties, however they were only 31.4% and 13.7% respectively of the Chinese wheat tested varieties. In addition, the proportion of phytoene synthase (PSY) allele, PPO allele and LOX active allele were roughly the same between Chinese and CIMMYT varieties. Based on the present study, we found that Pina gene had a greater impact on grain hardness value than Pinb gene; The influence of PPO-A1 gene on polyphenol oxidase activity was more significant than PPO-D1 gene. The high protein content of varieties mostly containing hardness genes and 1/2*/5+10 subunit combinations. Based on the present study, we found that the quality gene distribution of Chinese and CIMMYT varieties was quite different, for instance, the high-quality HMW-GS subunits of Chinese varieties were lower than CIMMYT lines. It will be much useful for Chinese wheat breeders to develop good quality wheat variety by crossing with 3 good strong gluten CIMMYT wheat lines by molecular marker-assisted selection.